2019
DOI: 10.1182/blood-2018-12-889725
|View full text |Cite
|
Sign up to set email alerts
|

NCAM1 (CD56) promotes leukemogenesis and confers drug resistance in AML

Abstract: Neural cell adhesion molecule 1 (NCAM1; CD56) is expressed in up to 20% of acute myeloid leukemia (AML) patients. NCAM1 is widely used as a marker of minimal residual disease; however, the biological function of NCAM1 in AML remains elusive. In this study, we investigated the impact of NCAM1 expression on leukemogenesis, drug resistance, and its role as a biomarker to guide therapy. Beside t(8;21) leukemia, NCAM1 expression was found in most molecular AML subgroups at highly heterogeneous expression levels. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 65 publications
3
46
0
1
Order By: Relevance
“…These data suggested that the three different FXIII-A expression profiles defined by FC might characterize novel subgroups of pediatric BCP-ALL [ 32 ]. Similar associations between expression intensity of biomarkers both at the mRNA and protein levels and clinical relevance have been observed to exist in T-ALL and in AML [ 33 , 34 ].…”
Section: Introductionsupporting
confidence: 60%
“…These data suggested that the three different FXIII-A expression profiles defined by FC might characterize novel subgroups of pediatric BCP-ALL [ 32 ]. Similar associations between expression intensity of biomarkers both at the mRNA and protein levels and clinical relevance have been observed to exist in T-ALL and in AML [ 33 , 34 ].…”
Section: Introductionsupporting
confidence: 60%
“…Interestingly, a recent study reported miR-7-5p has a role in regulating oxaliplatin, a platinum reagent, resistant in hepatocellular carcinoma (Hu, Yang, Li, & Zeng, 2018). In addition, miR-29a-3p was reported to regulate the response of chronic myeloid leukemia cell to tyrosine kinase inhibitor (Salati et al, 2017 and COL4A1 were associated with chemoresistant in human cancers (Gao et al, 2019;Huang, Gu, Sun, & Gao, 2018;Huy et al, 2018;Ju et al, 2017;Li et al, 2019;Ma et al, 2017;Sasca et al, 2019;Yadav, Kumar, Varshney, & Yadava, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…16 It is reported that NCAM1 has high expression in natural killer (NK) cells and AML patients. 17,18 Moreover, NCAM1 induces leukemogenesis and confers drug resistance to AML cells, 18,19 revealing a role of NCAM1 as a biomarker for the therapy of AML patients. Therefore, NCAM1 plays crucial role in AML cells.…”
Section: Introductionmentioning
confidence: 99%